Leader-follower of quadrotor micro aerial vehicle - Pebrianti, Dwi; Chun, Yee Woon; Hao, Yong Hooi; Qian, Goh Ming; Mahfuzah, Mustafa; Rosdiyana, Samad; Bayuaji, Luhur (UTeM, 2018)
A Micro Aerial Vehicle (MAV) is known as a drone or in a bigger size is called Unmanned Aerial Vehicle (UAV). Quadrotors are leading edge of a huge development in military and civilian such as disaster search and rescue, surveillance, aerial mapping and others. However, those applications limits by the payload delivered and long execution time. Hence, this study focuses on Leader-Follower approach of Quadrotor MAV. The study covers the development of quadrotor platform, modelling, controller design and leader-follower implementation. As the preliminary study, an Android phone is used as a leader which is used to provide the desired position and orientation to the follower quadrotor. The follower will be an autonomous quadrotor. Proportional Integral Derivative (PID) controller for the position and attitude control are first designed and tested via simulation. Then, a real flight implementation is conducted. The result shows that the follower can follow the leader on a circular path and straight line path. The settling time for X, Y and Z position of the follower is 10.22, 10.90 and 19.45 seconds, respectively. Additionally, the overshoot percentage for X, Y and Z position are 7%, 0% and 0%, respectively.